ANALISIS PENGARUH PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN DAN KESEHATAN, INFLASI DAN KEMISKINAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL MODERATING DI INDONESIA - Mahendra, A. (UNIKA Santo Thomas, 2020)
This research is intended to know the influence of government expenditure on education and health sector, inflation, and poverty on human development index with economic growth as a moderating variables in Indonesia. Population in this research is Indonesia and 20 of them were selected to be the samples for this research through purposive sampling technique. Estimates conducted by the multiple regression analysis. The data that were used in this study were secondary data, consisted of Government Expenditure, Inflation, and Poverty to human development index for the year 2000-2019. The results of this research, that Based on the partial test (t test), the Poverty variable has no significant effect while the Inflation and Government Expenditure variables have a significant effect on the variables of the human development index in Indonesia, the simultan test (F test), government expenditure, inflation, and poverty have a significant effect on the variables of the human development index. The economic growth variables are unable to moderate the relationship between government expenditure, inflation and poverty on the human development index.